Insurance distribution directive : a legal analysis - Marano, Pierpaolo; Noussia, Kyriaki (AIDA Europe Research Series on Insurance Law and Regulation, 2021)
This open access volume of the AIDA Europe Research Series on Insurance Law and Regulation offers the first comprehensive legal and regulatory analysis of the Insurance Distribution Directive (IDD). The IDD came into force on 1 October 2018 and regulates the distribution of insurance products in the EU. The book examines the main changes accompanying the IDD and analyses its impact on insurance distributors, i.e., insurance intermediaries and insurance undertakings, as well as the market. Drawing on interrelations between the rules of the Directive and other fields that are relevant to the distribution of insurance products, it explores various topics related to the interpretation of the IDD – e.g. the harmonization achieved under it; its role as a benchmark for national legislators; and its interplay with other regulations and sciences – while also providing an empirical analysis of the standardised pre-contractual information document. Accordingly, the book offers a wealth of valuable insights for academics, regulators, practitioners and students who are interested in issues concerning insurance distribution.